The role of infrastructure systems in improving the quality of maritime services A field study in the General Company for Ports of Iraq - Fadhel , Oday (The Gulf Economist, 2023)
The study aims to reveal and define the role of maritime services infrastructure in improving the quality of maritime services in Iraqi ports, and a questionnaire was developed to ensure the existence of a relationship between the study variables (maritime services infrastructure - an independent variable) and (improving the quality of maritime services - a dependent variable). The study concluded that there is a positive impact relationship with significant statistical significance for the maritime services infrastructure and its dimensions (maritime communications, specialized maritime units, maritime maintenance, specialized maritime staffs and crews) in improving the quality of maritime services, so the study recommended the need to pay attention to the maritime services infrastructure and benefit from The results of the study to enhance the status of Iraqi ports and the maritime crew in the field of competition in the maritime industry and the effective role of ports in the maritime transport industry..